ANALISA BIMBINGAN HIDUP SEHAT OLEH ORANG TUA SELAMA PANDEMI COVID-19 DI PERUMAHAN PRAMUKA KECAMATAN RUMBAI KOTA PEKANBARU - Sari, Maya; Chairilsyah, Daviq; Hukmi, Hukmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study aims to analyze the guidance of healthy living by parents, identify and analyze the factors that are constraints by parents and to determine the efforts made by parents in overcoming obstacles in providing healthy life guidance to children during the Covid-19 pandemic Pramuka Residence in Rumbai District, Pekanbaru City. The population in this study were the parents of the students at Pramuka Housing, Rumbai District. In determining the sample, the authors used purposive sampling technique. The sample used in this study is a housewife who lives in Pramuka Housing, Rumbai District, Pekanbaru City. The type of data used is primary data in the form of interviews and direct observations in the field, while secondary data comes from documentation and literature study. The data collection techniques used were observation and interviews. The data analysis technique used is a qualitative descriptive method that aims to provide a description of a particular symptom or phenomenon. The results showed that the guidance of healthy living by parents during the Covid-19 pandemic in the Pramuka Housing, Rumbai district, Pekanbaru City was carried out through direct communication accompanied by examples of direct actions from parents to children, but not all parents took it seriously.Key Words: Guidance, Healthy Living, Parents, Covid-19 Pandemic